An Investigation of University Students’ Attitudes Toward Environmental Sustainability - Şahin, Hande; Erkal, Sibel (European Journal of Sustainable Development, 2017)
The adoption of pro-environmental behavior is critical to reduce negative environmental impacts and move toward a more sustainable future. The role of higher education in training professionals to protect the environment for the future is important. The aim of the study was to investigate university students’ attitudes toward environmental sustainability. In this descriptive study, 212 students studying child development and social work at the Faculty of Health Sciences at Kirikkale University completed a questionnaire on demographic characteristics and the sustainable environmental attitude scale. Descriptive statistics (e.g., frequency and percentage distribution, arithmetic mean, standard deviation, etc.) and t-tests and an analysis of variance were employed to analyze the differences between groups. The mean for university students’ attitudes toward environmental sustainability was ± SD = 3.28 ± 0.26. The results revealed that the students studying child development ( ± SD = 3.31 ± 0.23) were more environmentally conscious than those studying social work ( ± SD = 3.2 ± 0.30) and that knowledge and the level of awareness affected environmental consciousness. It appears that the greatest challenges faced are the rapid changes in knowledge about environmental issues. These changes need to be included in the curricula of universities. Keywords: Environment, Sustainable Environment, Environmental Sustainability, University Students